PENGARUH UKURAN PERUSAHAAN, LEVERAGE DAN TIPE INDUSTRI TERHADAP CORPORATE INFORMATION TRANSPARENCY ON THE INTERNET (e-CTI) PERUSAHAAN LQ45 - Howard Sarmento Giam; Ririn Breliastiti (Jurnal Akuntansi Bisnis, 2017)
Science and technology is growing in line with the development of business and economics. The development of the Internet as a means to disseminate information about the company has created a form of communication between the company and its stakeholders. The company as a provider of financial data will reach a wider user when using the website.The fact that there are not all companies provide a website to inform the company to stakeholders led to the need for this research. The purpose of this study was to obtain empirical evidence about the factors that affect the company's disclosure of information via the Internet (website).Research conducted on 45 companies in the Indonesia Stock Exchange whose shares are listed in the LQ45. Hypothesis testing is done through either partial or simultaneously regression.Results of the study provide empirical evidence that the characteristics of the company consisting of firm size (SIZE), leverage (LEV) and type of industry (IND) simultaneously does not affect the e-CTI. However, for the partial test for this type of industry (IND) proved to yield significant results. That is, for companies that are in LQ45, type of industry influence on Internet-based information disclosure or use of the website. This proves that the company in a particular industry will reveal more information than other types of industries. Keywords: e-CTI, transparency, information.